14
$\begingroup$

Can the following integral be evaluated using complex method by substituting $\sin(x) = {e^{ix}-e^{-ix} \over 2i}$? $$ I=\int_0^{\pi/2} \ln ( \sin(x)) \; dx = - {\pi \ln(2) \over 2}$$

$\endgroup$
  • 2
    $\begingroup$ Are you sure you want to compute $I$ using "complex method"? $\endgroup$ – Did Sep 1 '12 at 10:35
  • 1
    $\begingroup$ I know how to calculate it with the other method. I'm just looking if it can be done. I don't have necessity to do it. $\endgroup$ – Monkey D. Luffy Sep 1 '12 at 10:55
  • $\begingroup$ Nice question (+1) $\endgroup$ – user 1357113 Sep 1 '12 at 11:03
  • $\begingroup$ @Chris'sister thank you ... :D $\endgroup$ – Monkey D. Luffy Sep 1 '12 at 11:04
  • 5
    $\begingroup$ This can be done with complex analysis, using the same exact method as my answer here. $\endgroup$ – Nick Strehlke Sep 1 '12 at 15:07
8
$\begingroup$

Note first that \begin{align*} \int_0^{2\pi} \ln(\sin t)\,dt &= 2\int_0^{\pi/2} \ln(\sin t)\,dt + 2\int_0^{\pi/2} \ln(-\sin t)\,dt \\ &= 2\int_0^{\pi/2} \ln(\sin t)\,dt + 2\int_0^{\pi/2} \Bigl(\ln(\sin t) + i\pi\Bigr)\,dt \\ &= 4I + \pi^2i \end{align*} and, using the substitution $z=e^{it}$ \begin{align*} \int_0^{2\pi} \ln(\sin t)\,dx &= \int_{|z|=1} \ln\left(\frac{z-1/z}{2i}\right)\,\frac{dz}{iz} \\ &= \int_{|z|=1} \frac{\ln(1-z^2)}{iz}\,dz - \int_{|z|=1} \frac{\ln z}{iz}\,dz + \int_{|z|=1} \frac{\ln(i/2)}{iz}\,dz. \end{align*}

The first integral on the right is zero $\dots$ this is because $\ln(1-z^2)$ is analytic inside the unit disk and vanishes at $z=0$ so the singularity in the integrand there is removable (you need to shrink the circle of integration slightly to avoid the points $z=\pm1$ and then let the radius go to 1).

The second integral we do directly $$ \int_{|z|=1} \frac{\ln z}{iz}\,dz = \left[\frac{1}{2i}\bigl(\ln z\bigr)^2\right]_{-1^+}^{-1^-} = \frac{1}{2i}\Bigl[(\pi i)^2 - (-\pi i)^2 \Bigr] = 0 $$ where $-1^\pm$ indicate points just above and below $-1$ and on either side of the branch cut of $\ln$ along the negative real axis.

The third integral is just $2\pi i\ln(i/2)/i = 2\pi\bigl(-\ln2 + \pi i/2\bigr)$.

Therefore $4I + \pi^2i = -2\pi\ln2 + \pi^2i$ and $I = -\frac{\pi}{2}\ln2$.

$\endgroup$
  • 1
    $\begingroup$ Nice! Would you mind writing a little more explanation of the step where you split the integral into three parts? $\endgroup$ – user29743 Sep 3 '12 at 20:16
4
$\begingroup$

Let us change variables $u=\sin^2(x)$, $x=\arcsin(\sqrt{u})$, $\mathrm{d}x = \frac{1}{2} \frac{\mathrm{d}u}{\sqrt{u(1-u)}}$: $$ \int_0^{\pi/2} \ln(\sin(x)) \mathrm{d}x = \int_0^1 \frac{1}{2} \ln(u) \cdot \frac{1}{2} \frac{\mathrm{d}u}{\sqrt{u(1-u)}} \stackrel{u=1-v}{=} \frac{1}{4} \int_0^1 \ln(1-v) \cdot \frac{\mathrm{d}v}{\sqrt{v(1-v)}} $$ Adding two last integrals, and dividing by $2$: $$ \int_0^{\pi/2} \ln(\sin(x)) \mathrm{d}x = \frac{1}{4} \int_0^1 \frac{\ln\left(\sqrt{u(1-u)}\right)}{\sqrt{u(1-u)}} \mathrm{d}u = -\frac{1}{4} \left.\frac{\mathrm{d}}{\mathrm{d}s}\operatorname{B}\left(s,s\right)\right|_{s=\frac{1}{2}} $$ Since $\operatorname{B}\left(s,s\right) = \frac{\Gamma(s)^2}{\Gamma(2s)}$: $$ \frac{\mathrm{d}}{\mathrm{d}s}\operatorname{B}\left(s,s\right) = 2 \operatorname{B}\left(s,s\right) \left(\psi(s) - \psi(2s)\right) $$ where $\psi(s)$ is the digamma function. Using $\operatorname{B}\left(\frac{1}{2},\frac{1}{2}\right) = \pi$, and duplication identity for the digamma function: $$ 2 \psi(2s) = \psi(s) + \psi\left(s+\frac{1}{2}\right) + 2 \log(2) \quad \stackrel{s=\frac{1}{2}}{\implies} \quad \psi\left(\frac{1}{2}\right) - \psi(1) = -2\ln(2) $$ Combining, we arrive at the result: $$ \int_0^{\pi/2} \ln(\sin(x)) \mathrm{d}x = \frac{1}{4} \cdot \pi \cdot \left(-2 \ln(2)\right) = -\frac{\pi}{2} \ln(2) $$

$\endgroup$
  • 1
    $\begingroup$ The OP explicitly requested a method using complex integration... $\endgroup$ – DonAntonio Sep 2 '12 at 2:13
0
$\begingroup$

Consider a known formula (which can be proved by the identity of $\sin x$ you mentioned):

$$ \prod_{j=1}^{n-1}\sin\left(\frac{j}{n}\pi\right)=\frac{n}{2^{n-1}}\quad n\geq 2, $$ which implies that $$ \frac{\pi}{2n}\sum_{j=1}^{n-1}\ln \left(\sin\frac{j}{n}\pi\right)=\frac{\pi}{2n}\ln (n)-\frac{\pi\cdot (n-1)}{2n}\ln 2. $$ Now taking the limit on both side as $n\to\infty$, you get what you want by recognizing that the left hand side is a Riemann sum.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.